Grammar guided embedding based Chinese long text sentiment classification. (7th June 2021) - Zhang, Chaoli; Lin, Dazhen; Cao, Donglin; Li, Shaozi
Abstract: Although the state‐of‐the‐art sentiment classification approaches, such as LSTM and TextCNN, have achieved a good performance on Chinese short text sentiment analysis, the Chinese long text sentiment classification is still a challenge because of the sentiment change problem and the long text structure problem. Therefore, we propose a grammar guided embedding model (GGE) and a novel Chinese long text sentiment classification framework. First, the part‐of‐speech (POS) tags are introduced as the Chinese long text grammar guided information which can help classification approaches to model the Chinese long text structure and the important structure of sentiment change. Second, we proposed a simple GGE training method which considers the combination representation of word sequence and POS sequence. Finally, we proposed a unified framework which combines our novel GGE with TextCNN. Experiment results show that after using GGE, the model outperforms the state‐of‐the‐art approaches. At the same time, we also found that the GGE achieves the model converge faster, that is, it can achieve better results than without GGE when there is only a small amount of training data. Thus, we believe that the GGE can help machines better understand human language sentiment expression structure.